The book of scenes for acting practice - Cassady, Marsh, 1936- 4 0 16; 5 (Lincolnwood, Ill., U.S.A. : National Textbook Co., 1985)
Contains selected scenes, grouped by the number of players, to sharpen acting skills. Includes a variety of styles, characters, and types of drama from Sophocles and Shakespeare to O'Neill and Ionesco.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Collections. -- Acting.;Drama;Acting.; 20; 2